Fiscal Decentralization: Is There a Simultaneous Relationship Between Regional Independence and Social Welfare? - Khoirunisa, Ika; Sulaeman, Agus Sunarya (Badan Pemeriksa Keuangan Republik Indonesia, 2022)
Indonesia's fiscal decentralization initiative aims for two essential goals to strengthen regional financial independence and social welfare. However, intergovernmental transfers could also reduce the urgency of local governments to increase their financial independence. This study is designed to prove whether intergovernmental transfers can improve regional financial independence and social welfare. Based on a statistical test of 500 districts/cities throughout 2017—2019 using multiple linear regression analysis, more than 90% of districts/cities have yet to achieve independent financial status. In addition, regional welfare in the country is still experiencing inequality. This study's result shows Revenue Sharing Fund (Dana Bagi Hasil, DBH), General Allocation Fund (Dana Alokasi Umum, DAU), and the previous year's Physical and Non-Physical Special Allocation Funds have a significant and positive effect on regional financial independence. However, only General Allocation Funds and Non-Physical Special Allocation Funds significantly and positively affect social welfare. Whereas Revenue Sharing Fund has an insignificant and negative effect, Physical Special Allocation Funds have a significant and negative effect on social welfare. Lastly, regional financial independence has a significant positive effect on social welfare.